Egg Characteristics of Pelung Chickens in Four Different Areas in West Java, Indonesia: technical inputs for conservation - Indrawati Yudha Asmara; Dani Garnida; Tuti Widjastuti; Iwan Setiawan; Wiwin Tanwiriah; Endang Sujana (Jurnal Ilmu Ternak, 2021)
Egg characteristics such as egg size and egg quality affect the hatchability rate of chicken eggs. The study objective was to determine egg characteristics of Pelung chickens that are endangered chickens of Indonesia. A total of 116 eggs from Garut, Bandung, Cianjur and Sukabumi Regencies, West Java Province, Indonesia was selected using a purposive technique. The observed parameters were egg weight, egg specific gravity, and thickness of an eggshell. Data were analyzed using the nonparametric Kruskal-Wallis test followed by the post hoc Mann-Whitney U test. The former was used to determine data differences among research areas, while the latter was applied to compare data differences between the two research areas. The rank Spearman analysis was used to determine the correlation between observed parameters. The study showed that there were significant differences (p > 0.05) among research areas for all observed parameters. Egg weight and thickness of eggshell in the Sukabumi Regency were higher than other regencies, while egg specific gravity in this regency was the highest (p > 0.05). There was a significant positive correlation (p > 0.05) between observed parameters. The findings indicated variation in the rearing management system and the genetic of Pelung chickens in research areas.